Arhitektura kot znanost v sistemu vrednotenja raziskovalnih dosežkov - Zupančič-Strojan, Tadeja (AR. Arhitektura, raziskave, 2004)
Proposed changes of the system for evaluation of scientific excellence in Slovenia are demanding reconsideration of relevant starting points for transforming scientific research criteria in architecture. Understanding of the scientific nature of architectural variety in its scientific (humanistic, social, technical etc.) and artistic dimensions triggers issues concerning architectural autonomy and its limitations in relation to other sciences. Favouring quantitative indicators and disregard for specifics of the profession are actually causing neglect for indicators of quality. In the quest for solutions that would limit anomalies, how can one insist on devising "uniform measures" without respect for differences between disciplines? The article checks the hypothesis about doubtfulness of generalising systems for raising the quality of scientific results in architecture. Alongside the review of tools for monitoring and evaluating scientific work and methods of their enforcement, most often mentioned in discourses about scientific research criteria in Slovenia, relations between quality and quantity as well as general and particular have been emphasised from the aspect of architecture as a science. The results can be useful for easier recognition of scientific components in a personal, architectural "opus" and stimulate the conscious formation of scientific components of ethical norms in Slovene architecture. They can enrich the promotion of science in architecture, as the creative starting point for development guidelines and potential artistic realisation.
Keywords: architecture; arhitektura; science; znanost; vrednotenje; Slovenia; Slovenija